The Influence of Website Quality, Ease of Use, and Customer Experience on Purchase Intention in Tokopedia E-Commerce: A Case Study of the Garu II Medan Amplas Community - Frian Danil; Rukmini Rukmini; Toni Hidayat; Melisa Zuraini Hasibuan; Ridho Mukti (International Forum of Researchers and Lecturers, 2025)
The objective of this research was to determine the influence of website quality, ease of use, and customer experience on purchase intention in Tokopedia e-commerce . The objectives include to determine the influence of website quality on purchase intention, to determine the influence of ease of use on purchase intention, and to determine the influence of customer experience on purchase intention. This study uses a descriptive quantitative approach with data collection methods of questionnaires, interviews, and documentation. The population in this study is the community of Jalan Garu II Medan Amplas and the sample as respondents of this study will be taken using probability sampling with the Slovin formula, namely 93 people who were met during the study. The data obtained in this study were analyzed using multiple linear regression analysis with the SPSS 26.0 program. The results of this study indicate that the calculated F value of 369.097 is greater than the F table of 2.474, which means that simultaneously there is an influence on website quality (X1), ease of use (X2), and customer experience (X3) on purchase intention in Tokopedia e-commerce. Partially, it can be seen that the website quality variables ( ¬X1), ease of use (X2), and customer experience (X3) have an effect on purchase intention (Y), namely the website quality variable (X1 ¬) of 3.227 is greater than the t table of 1.661, ease of use of 2.607 is greater than the t table of 1.661 and customer experience (X3) of 5.253 is greater than the t table of 1.661. Based on the results seen from the coefficient of determination of the website quality variables (X1 ¬), ease of use (X2), and customer experience (X3) have an effect, namely with an R2 value of 0.950 or 95%.